STAT6 Signaling Mediates PPARγ Activation and Resolution of Acute Sterile Inflammation in Mice - Ye-JI Lee; Bo-Min Kim; Young-Ho Ahn; Ji Ha Choi; Youn-Hee Choi; Jihee Lee Kang (Cells, 2021)
The signal transducer and activator of transcription 6 (STAT6) transcription factor promotes activation of the peroxisome proliferator-activated receptor gamma (PPARγ) pathway in macrophages. Little is known about the effect of proximal signal transduction leading to PPARγ activation for the resolution of acute inflammation. Here, we studied the role of STAT6 signaling in PPARγ activation and the resolution of acute sterile inflammation in a murine model of zymosan-induced peritonitis. First, we showed that STAT6 is aberrantly activated in peritoneal macrophages after zymosan injection. Utilizing STAT6−/− and wild-type (WT) mice, we found that STAT6 deficiency further enhanced zymosan-induced proinflammatory cytokines, such as tumor necrosis factor-α, interleukin (IL)-6, and macrophage inflammatory protein-2 in peritoneal lavage fluid (PLF) and serum, neutrophil numbers and total protein amount in PLF, but reduced proresolving molecules, such as IL-10 and hepatocyte growth factor, in PLF. The peritoneal macrophages and spleens of STAT6−/− mice exhibited lower mRNA and protein levels of PPARγ and its target molecules over the course of inflammation than those of WT mice. The deficiency of STAT6 was shown to impair efferocytosis by peritoneal macrophages. Taken together, these results suggest that enhanced STAT6 signaling results in PPARγ-mediated macrophage programming, contributing to increased efferocytosis and inflammation resolution.